2007
DOI: 10.1095/biolreprod.106.058172
|View full text |Cite
|
Sign up to set email alerts
|

Red Deer Cloned from Antler Stem Cells and Their Differentiated Progeny1

Abstract: The significance of donor cell differentiation status for successful cloning by somatic cell nuclear transfer (SCNT) is unclear. Here, we cloned a new species, red deer (Cervus elaphus), from multipotent antler stem cells and their differentiated progeny. Cultured donor cell lines from male antlerogenic periosteum (AP) were left undifferentiated or chemically induced to initiate osteogenesis or adipogenesis. Based on their morphology and marker gene expression profile, donor cells were classified as undifferen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
54
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(59 citation statements)
references
References 99 publications
(120 reference statements)
4
54
1
Order By: Relevance
“…The higher appropriate remodeling of stem cell-NT derived embryos has proved in different species (Bosch et al, 2006, Faast et al, 2006, Kumar et al, 2012, Lee et al, 2006, Rideout et al, 2000. Some reports, however, have rejected transcendence of stem cells over somatic cells in normal reprogramming of NT derived embryos (Berg et al, 2007, Li et al, 2013, Sung et al, 2006. In the first report on the use of bovine MSCs for NT, no priority in developmental potential was observed in stem cell derived embryos compared to non-stem cell derived counterparts (Kato et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The higher appropriate remodeling of stem cell-NT derived embryos has proved in different species (Bosch et al, 2006, Faast et al, 2006, Kumar et al, 2012, Lee et al, 2006, Rideout et al, 2000. Some reports, however, have rejected transcendence of stem cells over somatic cells in normal reprogramming of NT derived embryos (Berg et al, 2007, Li et al, 2013, Sung et al, 2006. In the first report on the use of bovine MSCs for NT, no priority in developmental potential was observed in stem cell derived embryos compared to non-stem cell derived counterparts (Kato et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Clearly, both populations of cells can give rise to chondrocytes (Fig. 6A) and osteoblasts, respectively, when in micromass culture (Li and Suttie, 2006) and in media containing dexamethasone and ascorbate (Berg et al, 2007). As both the pedicles and antlers are composed of cartilage and bone, it was not surprising to learn that the AP and the PP cells were able to differentiate into chondroblastic and osteoblastic lineages (Kierdorf et al, 1994;Li and Suttie, 1994).…”
Section: Adult Stem Cells With Embryonic Stem Cell Featuresmentioning
confidence: 99%
“…The differentiation potency of the AP and the PP cells has been investigated by several laboratories (Berg et al, 2007;Li and Suttie, 2006;Price et al, 2005). Clearly, both populations of cells can give rise to chondrocytes (Fig.…”
Section: Adult Stem Cells With Embryonic Stem Cell Featuresmentioning
confidence: 99%
“…It has been suggested that the (cambium layer of the) AP contains stem cells and that pedicle and first antler growth depend on the activation of these stem cells [14,15] . It was shown that cells from the AP express the transcription factor gene OCT-4 (POU5F1) and that the expression of this gene is downregulated in cultured AP cells upon differentiation into adipocytes [29] . More recently it was reported that cells from the AP also express considerable levels of the cell surface antigen CD9 [15] .…”
Section: Significance Of the Antlerogenic Periosteum For Pedicle And mentioning
confidence: 99%
“…More recently it was reported that cells from the AP also express considerable levels of the cell surface antigen CD9 [15] . Cells isolated from the AP of red deer (Cervus elaphus) could be induced to differentiate along different (osteoblastic and adipogenic) mesenchymal lineages in vitro [29] . An in vivo study applying AP cell labeling with the lacZ gene at the time of pedicle initiation observed ␤ -galactosidaseexpressing cells in mesenchyme, precartilage, cartilage, and bone (but not skin) of the growing appendage, thereby confirming the derivation of pedicles and first antlers from the AP [15] .…”
Section: Significance Of the Antlerogenic Periosteum For Pedicle And mentioning
confidence: 99%